The CMAR and extent of compliance with IFRS 101 standard among Malaysian ace market companies (Journal of Business Management and Accounting, 2012)
Malaysia is on the track to achieve full convergence and adoption of the InternationalFinancial Reporting Standards (IFRSs) by 2012. This study seeks to find out the extentof compliance with IFRS 101 ‘Presentation of Financial Statements’ before the effectivedate. Using total disclosure index (TDI), the findings shows that most of Malaysian AceMarket companies have complied with IFRS 101. The present study also indicates thatthe Cumulative Market Adjusted Return (CMAR) is positive and significant for bothpartial and full compliance of IFRS 101 among the Malaysian Ace Market companies.Multivariate regression analysis further provides a lack of significant associationbetween CMAR and announcement of earnings (i.e. EPS). Nevertheless, the percentageof independent directors on the board (BDIND) is found to be a positive and a significantcorporate governance variable that associates with CMAR. These findings imply thatpolicy makers and regulators should encourage Ace Market companies to have themost optimal number of independent board of directors for future improvements ofCMAR